2014
DOI: 10.1039/c4mb00435c
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in rat pulmonary phosphatidylcholines after chronic exposure to ambient fine particulate matter

Abstract: This study elucidated the underlying pathophysiological changes that occur after chronic ambient fine particulate matter (PM2.5) exposure via a lipidomic approach. Five male Sprague-Dawley rats were continually whole-body exposed to ambient air containing PM2.5 at 16.7 ± 10.1 μg m(-3) from the outside of the building for 8 months, whereas a control group (n = 5) inhaled filtered air. Phosphorylcholine-containing lipids were extracted from lung tissue and profiled using ultraperformance liquid chromatography-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 58 publications
3
9
0
Order By: Relevance
“…The decreasing level of three P-PCs, including PC(P-16:0/16:0), PC(P-16:1/20:3), and PC(P-38:5) in the tolerant group compared with the control group may imply that the consumption of sacrificial oxidants or scavengers against the naphthalene induced molecular perturbations to protect other membrane components. A similar reduction trend of P-PCs was also observed in the lungs of rats chronically exposed to ambient fine particulate matter [ 21 ]. In our previous study [ 14 ], an significant increase in acetone in the bronchoalveolar lavage fluid (BALF) from the same injured mice was found.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The decreasing level of three P-PCs, including PC(P-16:0/16:0), PC(P-16:1/20:3), and PC(P-38:5) in the tolerant group compared with the control group may imply that the consumption of sacrificial oxidants or scavengers against the naphthalene induced molecular perturbations to protect other membrane components. A similar reduction trend of P-PCs was also observed in the lungs of rats chronically exposed to ambient fine particulate matter [ 21 ]. In our previous study [ 14 ], an significant increase in acetone in the bronchoalveolar lavage fluid (BALF) from the same injured mice was found.…”
Section: Discussionsupporting
confidence: 70%
“…SMs not only play an important role in the membrane microenvironments (such as caveolae and lipid rafts) [ 18 ] but also in the precursor pool of second messengers for cellular signal transduction [ 19 ]. Previously, our laboratory developed a validated liquid chromatography-tandem MS platform to monitor the alterations of different phosphorylcholine-containing lipids and apply them in studying pulmonary toxicity [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, another study found that PM 2.5 decreased the levels of these metabolites in pulmonary tissue [17]. In that study, PM 2.5 was given to rats through ambient air for 8 months and histopathology revealed emphysema [17]; however, in our study, PM 2.5 was given to rats through acute instillation, and histopathology only exhibited edema and infiltration of PMNs in the alveolar septum, which is a different stage of PM 2.5 -induced pulmonary injury. In the early stage of pulmonary injury, the elevation of LPC and PC levels was a response to PM 2.5 stimulation.…”
Section: Discussionmentioning
confidence: 92%
“…The imbalance of Cer and S1P leads to alveolar enlargement or fibrosis and is involved in the onset of COPD, asthma, lung fibrosis and lung cancer [16]. Although a phospholipid metabolism profile of pulmonary tissue after PM 2.5 exposure has been carried out [17], the global lipid metabolism change induced by PM 2.5 is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that vascular endothelial growth factor receptor (VEGF), mitogen-activated protein kinase (MAPK), nuclear factor κB (NF-κB) and interleukin (IL)-8 signaling is involved in PM2.5-induced lung injury (8). In PM2.5-exposed rats, a decrease in phosphatidylcholine levels may be detected, which may impair alveolar type II cells and alter cell functions (9). In addition, PM2.5 exposure has been demonstrated to be associated with endothelial cell…”
Section: Introductionmentioning
confidence: 99%